Convergence of calculated dislocation core structures in hexagonal close packed titanium. (5th December 2017) - Poschmann, Max; Asta, Mark; Chrzan, D C
Abstract: The core structure of ⟨ a ⟩ -type screw dislocations in hexagonal close packed titanium is investigated computationally using periodic supercells with quadrupolar configurations in combination with density functional theory (DFT) and a modified embedded atom method (MEAM) classical potential. Two arrangements of the quadrupolar supercell configurations are examined, and within each arrangement two initial dislocation positions are compared. (Meta)stable pyramidal and prismatic dislocation core structures exist within both DFT and MEAM methods, and the relaxed structure from a given configuration resulting from our anisotropic elasticity theory solution depends only on the assumed initial dislocation positions. Within DFT we find the ground state core structure to be spread on the pyramidal plane. We find that it is necessary to include the semi-core 3 p electrons as valence states in the DFT calculations in order to converge the ground state dislocation core configuration and difference in energy between structures. In terms of k -point sampling, it is found that at least a 1 × 1 × 15 k -point mesh is necessary to converge the dislocation core structure for a supercell one Burgers vector deep. Use of higher k -point densities or inclusion of additional semi-core electronic states as valence electrons results in the same core structure. With the MEAM potential considered in this work, we find the ground state core configuration to be spread predominantly on the prismatic plane, in contrast with the DFT results.